Computational Thinking Integration into Middle Grades Science Classrooms: Strategies for Meeting the Challenges - Danielle Cadieux Boulden; Eric Wiebe; Bita Akram; Osman Aksit; Philip Sheridan Buffum; Bradford Mott; Kristy Elizabeth Boyer; James Lester (Middle Grades Review, 2018)
This paper reports findings from the efforts of a university-based research team as they worked with middle school educators within formal school structures to infuse computer science principles and computational thinking practices. Despite the need to integrate these skills within regular classroom practices to allow all students the opportunity to learn these essential 21st Century skills, prior practice has been to offer these learning experiences outside of mainstream curricula where only a subset of students have access. We have sought to leverage elements of the research-practice partnership framework to achieve our project objectives of integrating computer science and computational thinking within middle science classrooms. Utilizing a qualitative approach to inquiry, we present narratives from three case schools, report on themes across work sites, and share recommendations to guide other practitioners and researchers who are looking to engage in technology-related initiatives to impact the lives of middle grades students.
Keywords: technology integration; computational thinking; computer science; science education